2022
DOI: 10.1055/a-1811-7948
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of the Hydroxycinnoline Core via Hydrazide-Assisted Rh(III)-Catalyzed C–H Functionalization and Annulation

Abstract: The structural modification of phthalazinones and indazolones has emerged as a pivotal topic in the catalytic C–H functionalization event. Herein we report the hydrazide-assisted rhodium(III)-catalyzed cross-coupling reactions of N-aryl phthalazinones and N-aryl indazolones with vinylene carbonate. This method provides direct access to tetracyclic hydroxycinnolines. Complete site-selectivity and functional group compatibility were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Based on the preliminary mechanistic experiments and previous reported literatures a plausible catalytic cycle pathway was proposed in Scheme . The active catalyst Cp*Rh­(III) species I was generated by ligand exchange with [Cp*RhCl 2 ] 2 , AgSbF 6 , and additive NaOAc, followed by the formation of the key rhodium complex II with the substrate 1a via a concerted C–H activation process.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the preliminary mechanistic experiments and previous reported literatures a plausible catalytic cycle pathway was proposed in Scheme . The active catalyst Cp*Rh­(III) species I was generated by ligand exchange with [Cp*RhCl 2 ] 2 , AgSbF 6 , and additive NaOAc, followed by the formation of the key rhodium complex II with the substrate 1a via a concerted C–H activation process.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Because of their versatile applications and pharmacological activities, various synthetic methods for functionalized and fused indazolones have been established . Recently, by using Rh­(III), Ir­(I), and Pd­(II) catalysts, indazolones could act as credible directing groups to synthesize indazolone-fused heterocycles in a tandem manner with high sustainability (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, simple tuning of reaction parameters could also selectively yield the dehydrated product (Scheme 11, top). 51,52 Control experiments showed that only in the presence of a Rh(III) catalyst, the hydroxyl group on 32a was readily eliminated to result in 33a smoothly. Additionally, the AgSbF 6 additive also enabled the synthesis of the vinylation product in a decent yield while the comparatively neutral AgOAc did not induce the dehydration process.…”
Section: With N Nucleophilesmentioning
confidence: 99%
“…Alternatively, simple tuning of reaction parameters could also selectively yield the dehydrated product (Scheme 11, top). 51,52…”
Section: [3 + 2]/[4 + 2] Cyclizationmentioning
confidence: 99%
“…Mechanistically, VC also shows an entirely different reaction pathway compared to the existing carbonates, thus resulting in a great number of exquisite organic transformations. Currently, there are three predominant categories of VC transformations: (1) transformations in which VC acts as a vinylation reagent to accomplish C–H [ n +2] endo -cyclization to rapidly construct various carbon- or hetero-cycles such as isocoumarins, 7 isoquinolinones, 8 indoles, 9 quinolines 10 and others 11 (Scheme 1b); (2) transformations in which VC functions as a one-carbon unit for C–H [ n +1] exo -cyclization to deliver heteroarenes via an acylation process 12 (Scheme 1c); and (3) transformations in which VC behaves as an acylmethyl linear synthon or analogue to execute C–H alkylation 13 (Scheme 1d).…”
mentioning
confidence: 99%